2005
DOI: 10.1016/j.resmic.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between inhibition of bacterial adhesion to a solid surface by sub-MICs of antibiotics and subsequent development of a biofilm

Abstract: Many studies have demonstrated that subminimal inhibitory concentrations (sub-MICs) of antibiotics can inhibit initial microbial adherence to medical device surfaces. It has been suggested that, by inhibiting initial adhesion, biofilm formation might be prevented. However, since initial adherence and subsequent biofilm formation may be two distinct phenomena, conclusions regarding the effects of sub-MIC antibiotics on initial adhesion cannot be extrapolated to biofilm formation. In this study, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 30 publications
9
36
0
Order By: Relevance
“…Previous reports suggested that the use of sub-MIC concentrations of antibiotics could increase biofilm formation (35). However, more recent studies demonstrated that sub-MIC concentrations of some antibiotics are effective for reducing the amount of biofilm formed (6,17,34,43), which may have some clinical interest. However, other changes that can occur in the physiology of biofilm cells might compromise the general use of this strategy to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggested that the use of sub-MIC concentrations of antibiotics could increase biofilm formation (35). However, more recent studies demonstrated that sub-MIC concentrations of some antibiotics are effective for reducing the amount of biofilm formed (6,17,34,43), which may have some clinical interest. However, other changes that can occur in the physiology of biofilm cells might compromise the general use of this strategy to prevent biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of dicloxacillin used in this study was 8 g/ml, which is a sub-MIC concentration, as determined in a previous study (6). Bacterial growth parameters were determined by monitoring the increases in the optical densities at 640 nm of cell suspensions grown in TSB in the presence and absence of dicloxacillin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicloxacillin is the antibiotic that found to prevent the adherence to the greatest extent when it is used alone at 1/2 of the MIC (Cerca et al, 2005). Also clindamycin at subinhibitory concentrations inhibits the adherence of Pseudomonas aeruginosa, Staphylococcus aureus, Bacteroids spp., Escherichia coli to bone surfaces (Lambe et al, 1987).…”
Section: A Antimicrobial Agentsmentioning
confidence: 99%
“…Yet the action of antimicrobial substances on biofilm density and bacterial growth and the interplay of bacteria, surfaces, antimicrobials at differential concentrations, and the host interfering with leukocytes, platelets, red blood cells, and fibrin-either combating or enhancing the bacterial resistance within the biofilm-is still controversial. Although adhesion may be reduced by coating surfaces with antibiotics or silver, biofilm formation and the subsequent infection of the implant are not predictable, as shown in experimental and clinical studies (4,11).…”
Section: Discussionmentioning
confidence: 99%